Pelatihan Buzz Marketing Pada Sepatu Adidas - Bambang Hengky Rainanto; Febri Damatraseta; Rafli Pradana (Jurnal Abdimas Dedikasi Kesatuan, 2021)
Buzz Marketing or word of mouth is an important attribute of Buzz Marketing. There are four attributes in Brand Equality from Brand Awareness , namely Association Brand ,, apartPrecieved Quality (perceived quality), Brand Loyalty (Brand Loyalty) and Other Proprientary Brand Assets (brand assets). other). There are four levels in Buzz Marketing, namely: Top Of Mind , Brand Recall , Brand Recognition , and Unware of Brand . In this review, it only focuses on "Overview of Buzz Marketing in Adidas Shoes", the purpose of this final project is to find out where Adidas is in thePyramid Buzz Marketing. Based on the research results show that Buzz Marketing has an important role in the introduction of adidas shoe products. Good marketing quality can foster high customer satisfaction. Keywords: Buzz Marketing, Top of Mind, Brand Recall, Brand Recognition Unaware of Brand